Flood shelters in Bangladesh: some issues from the user's perspective - Rahman, Mohammad Aminur; Mallick, Fuad Hassan; Mondal, M. Shahjahan; Rahman, Rezaur (© 2015 Elsevier Inc., 2016)
This article was published in Hazards, Risks and, Disasters in Society [© 2015 Elsevier Inc.] and the definite version is available at : http://www.sciencedirect.com/science/article/pii/B9780123964519000093